Rich man, poor man, middleman, thing: Distributing power. (September 2021) - Hertz, Ellen
The author reviews the fine ethnographic analyses in this special issue and argues that they become more coherent if power is understood as a sociotechnological network. This further implies that anthropologists' conclusions about how power is exercised must be modest, both historically situated and politically targeted, if the discipline wishes to contribute meaningfully to holding the powerful to account.